Opinion Mining Using Sequence Labeling - Lakshmi, Vijiya; M.S., Vijaya (Transactions on Engineering and Computing Sciences, 2015)
Opinion mining aims to determine the attitude of a person by identifying and extracting subjective information. The attitude is the judgement, evaluation or emotional state of the person towards a product, or service or a person. An essential task in opinion mining is to classify the polarity of a review at the document, sentence, or feature level whether the expressed opinion is positive, negative or neutral. The main objective of this research work is to formulate opinion mining task as sequence labelling and to build the models for classifying the opinion about the product Kingston Pen drive review as positive or negative. The performances are evaluated and the comparative results are analyzed and reported.